Once a Plagiarist, Always a Plagiarist - Muhammad Sameer Qureshi (Journal of the Dow University of Health Sciences, 2014)
Well, not really. But the above title certainly directs the reader towards the actual adage: once a thief, always a thief. Does this make both the words (plagiarist and thief) synonymous? In a way, yes, it does. Derived from the Latin words plagiare (to kidnap) and plagiatum (stealing people), the word plagiarism is defined as: “…the use of others’ published and unpublished ideas or words (or other intellectual property) without attribution or permission, and presenting them as new and original rather than derived from an existing source.”